Investigating The Role of viral marketing, online consumer reviews and prices on online shop purchasing decisions - Martias, Dony (International Journal of Social and Management Studies, 2023)
- The purpose of this study is to analyze the relationship between Viral marketing and Purchasing Decisions, Online Consumer Reviews on Purchasing Decisions, Price and Purchase Decisions. The research method is a quantitative survey. The research data was obtained by distributing online questionnaires to 560 onlineshop consumers. Data analysis used structural equation modeling ( SEM) with SmartPLS 3.0 software tools. The stages of data analysis are validity, reliability and significance tests. The sampling technique used is non-probability sampling. The questionnaire used in this study uses the Google form, which will be distributed to respondents. The measurement method for this questionnaire uses a Likert scale of 5, namely Strongly Disagree (STS), (2) Answers Disagree (TS), (3) Neutral Answers (N), (4) Answers Agree (S), Strongly Agree (SS). ). The results of this study are Viral marketing has a positive and not significant effect on Purchasing Decisions, Online Consumer Reviews has a positive and significant effect on Purchasing Decisions, Price has a positive and significant effect on Purchase Decisions.